Effect of the DGAT1 K232A mutation and breed on milk traits in cattle populations of Ethiopia - Samuel, Behailu; Dadi, Hailu; Dinka, Hunduma (Frontiers in Animal Science, 2023)
Non-conservative K232A substitution in the diacylglycerol acyl-CoA acyltransferase 1 (DGAT1) gene has been reported to explain variation in milk traits in cattle. The objective of this study was to estimate allele and genotype frequencies and to assess associations between K232A variants and milk yield and composition in cattle populations of Ethiopia. Blood samples for genomic DNA extraction and milk samples for analysis of milk components were collected from 92 randomly selected cattle of five Ethiopian breeds. Gene-specific primers were used to amplify 278 bp of the exon 8 region of DGAT1. Allele and genotype frequencies were calculated using Power Marker, and the GLM function of SAS software was used to assess the associations of detected genetic variation with milk traits. Boran * Holstein Friesian (HF) crosses produced a higher daily milk yield than the other breeds (p< 0.05), whereas the Boran and Begait breeds produced milk with higher fat and protein contents (p< 0.05), and Horro produced milk with a higher content of lactose, than the other breeds studied (p< 0.05). Alleles K and A and genotypes AA, KA, and KK were detected. The frequency of K232 ranged from 0.50 in Boran * HF crosses to 0.97 in the Horro population. The frequency of the KK and KA genotypes in the zebu population ranged from 0.50 to 0.94 and from 0.03 to 0.50, respectively. The AA genotype was associated with higher milk yield in Boran * HF crosses, whereas the KA genotype was associated with higher milk yield in the zebu populations (p< 0.05). The fat and lactose contents of milk produced with the KA genotype were lower than those of milk produced with the KK genotype in all genetic groups (p< 0.05). Substitution of one copy of the K allele led to a significant (p< 0.05) increase in fat content, of up to 0.81%, a decrease in daily milk yield of up to 3 L, and a decrease in lactose content of 0.58% in the sampled populations. The association study confirmed that the DGAT1 K232A marker had significant effects on daily milk yield, milk fat and lactose contents in the investigated cattle. These results suggested that the DGAT1 K232A marker may be utilized to accelerate future molecular breeding of dairy cattle, tropical zebu, their crossbreeds, after validation in a larger population.